Health Literacy Needs Among Unemployed Persons: Collating Evidence Through Triangulation of Interview and Scoping Review Data - Samkange-Zeeb, Florence; Singh, Hunny; Lakeberg, Meret; Kolschen, Jonathan; Schüz, Benjamin; Christianson, Lara; De Santis, Karina Karolina; Brand, Tilman; Zeeb, Hajo (Frontiers in Public Health, 2022)
Background: Unemployed persons are at high risk for low health literacy. Most studies addressing health literacy of unemployed persons focus on risk factors for low health literacy or correlates of health literacy, but studies on needs of unemployed persons regarding health literacy are scarce. We aimed to obtain better understanding of health literacy needs of unemployed adults by triangulating the results from a scoping review on health literacy needs in unemployed adults and additional in-depth qualitative interviews. Methods: Scoping review: We searched six databases up to January 2021 as well as grey literature for relevant studies following PRISMA-ScR guidelines. Titles, abstracts, and full texts were screened independently by two researchers. Qualitative study: Ten participants of a job-reintegration program in Germany were interviewed following a guideline covering topics including health issues of interest to the participants, their sources of health-related information and the barriers/facilitators they experience when accessing health services. Results: Scoping review: After screening 2966 titles and abstracts, 36 full texts were considered, and 5 articles fulfilled the inclusion criteria. Four focused on mental health literacy and outcomes, while the fifth assessed information-seeking practices. One additional report on health literacy was identified via the grey literature search. Awareness of one’s condition was identified as a facilitator for mental health help-seeking, while fear of harmful effects of medication prevented help-seeking. Qualitative study: Participants were interested in and were generally well-informed about health topics such as nutrition and physical activity. The main challenge perceived was translating the knowledge into practice in daily life. GPs and the social services providers played an important role as a source of health information and advice. Regarding mental health, similar barriers, facilitators and needs were identified through triangulation of findings of the scoping review with those of the interviews. Conclusions: There is need to address health literacy needs of long-term unemployed persons that go beyond mental health literacy. Public health interventions should not only aim at improving health literacy scores, but also focus on how to help participants translate health literacy into practice. Population groups of interest should also be involved in all processes of designing interventions.